INSTITUTIONALIZATION OF STRATEGIC PLANNING OF FOREIGN ECONOMIC POLICY: THE SWISS EXPERIENCE AND PROSPECTS FOR UKRAINE - Тетяна Гудіма; Владислав Камишанський; Веста Малолітнева (Фінансово-кредитна діяльність: проблеми теорії та практики, 2022)
The article is devoted to the analysis of institutionalization features of strategic planning of economic policy, particularly Ukrainian foreign economic policy, identifying problems in this direction and forming proposals for their decision. Using the comparative method, the experience of strategic planning of Swiss foreign economic policy, as a country that undoubtedly deserves the status of one of the world's leading economic centers, and Ukraine is analyzed and compared. It is proved that the lack of institutionalization of strategic planning in Ukraine leads to a breach of consistency and coherence in the implementation by state authorities as economic policy in general, and its separate directions, in particular the foreign economic policy. Based on the Swiss experience, the expediency of using the cascade model in the process of strategic planning for the implementation of state foreign policy, as well as of Ukrainian legal regulation modernization by strengthening the legal mechanisms of adoption of strategic documents is argued.